Uji efektivitas senyawa antibakteri penyebab ice-ice dari daun ketapang Terminalia catappa L. dengan metode ekstraksi berbeda - Sinaga, Chintya R.; Kreckhoff, Reni L.; Salindeho, Indra R. N.; Ngangi, Edwin L. A.; Mudeng, Joppy D.; Rompas, Rizald M. (Universitas Sam Ratulangi, 2022)
This study aimed to find out the right extraction method to produce ketapang leaf extract with best phytochemical content and best inhibition ability against ice-ice causing bacteria. The experiment was conducted at the Laboratory of Fish Health, Environmental and Toxicology, from April to June, 2021. The experiment was designed according to a Completely Randomized Design (CRD) with 5 treatments and 3 replications. The three main treatments were, treatment A: extraction of ketapang leaves Terminalia catappa L. with 95% ethanol (extract A), treatment B: extraction of ketapang leaves T. catappa L. with 40°C water (extract B), and treatment C, extraction of ketapang leaves T. catappa L. with distilled water (extract C). In the inhibition ability test, each extract obtained from the three main treatments was compared with two controls namely treatment D: positive control (Kanamicyn) and treatment E: negative control (aquadest). The phytochemical content data was analyzed descriptively, while the bacterial inhibition zone diameter data was statistically analyzed with Anova and LSD. The phytochemical analysis result showed that, the extract A contains alkaloids, flavonoids, triterpenoids and tannins, while extract B and extract C contain alkaloid, saponin and tannin. The inhibition ability test showed that extract A gave the strongest inhibition (14.87 mm) against the ice-ice causing bacteria, and was significantly different from that of extract B (5.23 mm) and C (2.47 mm). The inhibition ability of extract B was significantly different from that of extract C. The inhibition ability of the three ketapang leaf extracts (A, B and C) against the ice-ice causing bacteria was much weaker and significantly different from that of Kanamicyn (positive control).